Supersonic Plasma Spray Deposition of CoNiCrAlY Coatings on Ti-6Al-4V Alloy - Caliari, F. R.; Miranda, F. S.; Reis, D. A.P.; Essiptchouk, A. M. [UNESP]; Filho, G. P. (Springer Nature, 2017)
Plasma spray is a versatile technology used for production of environmental and thermal barrier coatings, mainly in the aerospace, gas turbine, and automotive industries, with potential application in the renewable energy industry. New plasma spray technologies have been developed recently to produce high-quality coatings as an alternative to the costly low-pressure plasma-spray process. In this work, we studied the properties of as-sprayed CoNiCrAlY coatings deposited on Ti-6Al-4V substrate with smooth surface (Ra = 0.8 μm) by means of a plasma torch operating in supersonic regime at atmospheric pressure. The CoNiCrAlY coatings were evaluated in terms of their surface roughness, microstructure, instrumented indentation, and phase content. Static and dynamic depositions were investigated to examine their effect on coating characteristics. Results show that the substrate surface velocity has a major influence on the coating properties. The sprayed CoNiCrAlY coatings exhibit low roughness (Ra of 5.7 μm), low porosity (0.8%), excellent mechanical properties (Hit = 6.1 GPa, Eit = 155 GPa), and elevated interface toughness (2.4 MPa m1/2).
Keywords: axial injection; CoNiCrAlY; overlay coating; supersonic plasma spray